Tundish spray coating
By using 800 mesh 95 magnesium sand, 600 mesh quicklime, silicon whiskers and composite hydrophobic agents in the tundra spray coating, the problem of difficulty in controlling the water content of traditional spray coatings is solved, and the fire resistance and crack resistance are significantly improved , extends service life and reduces production costs.
Patent Information
- Application Number
- CN202411338481.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Traditional tundra magnesium spray coatings have difficulty in controlling the amount of water added during construction, which leads to cracking and peeling of the spray coating layer, reducing service life and safety, and evaporation of moisture causes thermal shock cracks, affecting fire resistance and stability.
Using 800 mesh 95 magnesium sand and 600 mesh quicklime ultrafine powder, silicon whiskers, composite hydrophobic agents and sodium metasilicate, polyvinyl alcohol, and sodium tripolyphosphate combination formula to improve the fire resistance and density of spray coatings , structural stability and crack resistance, reduce water addition, enhance construction performance and corrosion resistance.
It significantly improves the fire resistance, density and crack resistance of spray coatings, extends service life, reduces the risk of cracking after drying, improves construction efficiency and product quality, and reduces production costs.
Smart Images

Figure BDA0005058964130000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tundish refractory materials, and in particular relates to a tundish spray coating. Background Art
[0002] In the modern continuous steel casting process, the tundish is the key link between the ladle and the crystallizer. The quality of its refractory materials is directly related to the quality of the casting, production efficiency and cost control. The tundish magnesium spray coating is widely used in the lining protection of the tundish due to its excellent high temperature resistance, slag erosion resistance and good construction performance; however, the control of the amount of water added during the construction of traditional magnesium spray coatings has always been one of the key factors affecting its final performance.
[0003] At present, magnesium spray coatings on the market generally require a water content between 16% and 22%, and even up to 25% in some cases, to ensure that the spray coating has good construction fluidity and adhesion to the permanent layer substrate. Although this high-water addition construction method temporarily meets the needs of construction convenience, it is accompanied by serious performance disadvantages. First, excessive water addition will cause a large amount of water evaporation stress inside the spray coating layer during the drying process, which will in turn cause the spray coating layer to crack, and even peel off in severe cases, greatly reducing its service life and safety; secondly, excessive evaporation of water will also leave pores inside the spray coating layer. These tiny defects become the germination points of thermal shock cracks, further weakening the overall strength and thermal shock resistance of the spray coating layer; in addition, residual water may also react with certain components in the refractory material to form a low melting point phase, reduce the refractoriness, and affect its stability and service life under high temperature conditions.
[0004] In view of the above technical difficulties, scientific research institutions and production enterprises in this field have actively engaged in the research of reducing the amount of water added during construction while ensuring the performance of spray coatings. These research efforts mainly focus on the following aspects: First, the innovative development of binders, aiming to reduce the water demand while maintaining or even improving the construction smoothness and high-temperature stability of spray coatings by introducing new binders such as organic resins and phosphates; second, the fine adjustment of particle grading, by optimizing the ratio of refractory aggregates and fine powders, achieving higher packing density and filling efficiency, thereby reducing dependence on water without affecting the convenience of construction. ; Third, the clever application of additives, by adding specific activators, expanders or fiber materials, the wet and dry strength of the spray coating can be enhanced, and the cracks caused by water evaporation can be effectively reduced; Fourth, the innovative design of the formula, such as the development of new magnesium spray coating formulas such as magnesium-calcium composite materials, through the modification of the material itself, fundamentally reducing the use of water and significantly improving the overall performance of the material; Although the above efforts have alleviated the problems caused by high moisture to a certain extent, there is no technology that can comprehensively solve the high moisture dependence in the construction process and at the same time meet the stringent requirements of industrial production for high performance of refractory materials. Summary of the invention
[0005] In view of the problem that the amount of water added to the existing tundish spray coating during the construction process causes poor construction performance and insufficient strength of the spray coating layer, the present invention provides a tundish spray coating, which overcomes the defects of the traditional tundish spray coating in controlling the amount of water added, can significantly improve the construction performance and strength of the tundish spray coating, and effectively prolong the service life of the tundish spray coating.
[0006] The scheme adopted by the present invention to solve the technical problem is: a tundish spray coating, wherein the mass percentages of the raw material components in the tundish spray coating are: 3-1mm 91 magnesia is 22-25%, 1-0mm 94 magnesia is 46-51%, 200 mesh 94 magnesia is 16-20%, 800 mesh 95 magnesia is 1.5-3%, silica fume is 2-3%, quicklime is 2-3%, silicon whisker is 0.1-0.15%, 70 cement is 0.4-0.6%, sodium metasilicate nonahydrate is 0.6-0.8%, polyvinyl alcohol is 0.3-0.5%, composite hydrophobic agent is 0.01-0.03%, paper fiber is 0.5-0.7%, organic fiber is 0.01%, metal aluminum powder is 0.02-0.03%, sodium tripolyphosphate is 0.2-0.3%, and citric acid is 0.1-0.3%.
[0007] Furthermore, the tundish spray coating comprises 23% of 3-1 mm 91 magnesia sand, 49% of 1-0 mm 94 magnesia sand, 18% of 200 mesh 94 magnesia sand, 2% of 800 mesh 95 magnesia sand, 2.4% of silica fume, 2.7% of quicklime, 0.12% of silicon whisker, 0.5% of 70 cement, 0.7% of sodium metasilicate nonahydrate, 0.43% of polyvinyl alcohol, 0.02% of composite hydrophobic agent, 0.6% of paper fiber, 0.01% of organic fiber, 0.02% of metal aluminum powder, 0.3% of sodium tripolyphosphate, and 0.2% of citric acid.
[0008] Furthermore, the sum of the mass percentages of 800-mesh 95 magnesia sand, silica fume and quicklime in the tundish spray coating is 6.2-8.4%.
[0009] Furthermore, the SiO2 content in the silica ash is ≥94%; the quicklime particle size is 600 mesh and the purity is 98%.
[0010] Furthermore, the SiO2 content in the silicon whisker is ≥99.9%, the fiber length is 2-10 μm, and the bulk density is 0.78 g·cm 3 , the true density is 2.2~2.4g·cm 3 , refractoriness is 1720℃, Mohs hardness is 7, and loss on ignition is ≤0.10%.
[0011] Furthermore, the composite hydrophobic agent has the following raw material components in percentage by weight: 75% polydimethylsiloxane and 25% fluorine-modified polyurethane.
[0012] Furthermore, the sodium metasilicate nonahydrate, polyvinyl alcohol, sodium tripolyphosphate and citric acid in the tundish spray coating are all of industrial grade.
[0013] Furthermore, the sum of the mass percentages of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate in the tundish spray coating is ≥1.15%.
[0014] Furthermore, the metal aluminum powder has a particle size of 80 mesh and an Al content of ≥98%.
[0015] The present invention adopts 800-mesh 95 magnesia sand and 600-mesh quicklime ultrafine powder, mainly to improve the performance of the spray coating and optimize the molten steel purification ability, wherein the 800-mesh 95 magnesia sand has the function of improving the refractoriness of the spray coating, enhancing the density and structural stability of the spray coating, and improving the thermal conductivity. The 95 magnesia sand is smelted at high temperature, has complete crystallization, high purity, and contains less impurities, so it can significantly improve the refractoriness and erosion resistance of the spray coating, especially in the face of continuous impact of high-temperature molten steel, it can effectively prevent thermal shock damage. The fine powder with a particle size of 800 mesh helps the spray coating to form a denser working layer, reduce porosity, and enhance the overall stability and permeability resistance of the spray coating layer, which is very important for preventing the penetration and erosion of non-metallic inclusions in molten steel. In addition, the high-purity 95 magnesia sand can improve the spray coating. Thermal conductivity helps to distribute heat more evenly and reduce damage caused by local overheating; 600-mesh quicklime can promote the sintering and hardening of the spray coating layer, adjust the matrix alkalinity, and improve the construction performance. After quicklime is added to the spray coating, it will quickly release heat and convert into slaked lime when it meets water. This process is accompanied by volume expansion, which helps the bonding and rapid solidification between the spray coating layers, and improves the overall strength and anti-flaking of the spray coating layer. Quicklime, as an alkaline substance, can adjust the alkalinity of the spray coating, which is very effective in inhibiting certain acid corrosion (such as sulfides in molten steel), and is conducive to protecting the tundish spray coating layer from corrosion. In addition, appropriate addition of quicklime can also improve the construction performance of the spray coating, such as improving its fluidity and wall hanging, making the spray coating easier to spray and evenly covered, ensuring the continuity and integrity of the spray coating layer. These two ultrafine powders work together in the magnesium spray coating through their unique physical and chemical properties, effectively improving the fire resistance, structural strength and corrosion resistance of the coating, and can also optimize the construction process.
[0016] The addition of silicon whiskers as a reinforcing phase in the present invention can further improve the mechanical properties and thermophysical properties of the spray coating. First, the addition of silicon whiskers as a reinforcing phase to the magnesium spray coating can significantly enhance the crack propagation resistance and overall mechanical strength of the spray coating by bridging cracks, dispersing stress concentration points, etc., thereby effectively improving the wear resistance and impact resistance of the spray coating layer and extending the service life of the spray coating. Secondly, in view of the low thermal expansion coefficient of silicon whiskers, incorporating them into the magnesium material can effectively adjust the thermal expansion behavior of the overall material, reduce the internal stress caused by rapid temperature changes, enhance the ability of the spray coating to resist thermal shock damage, and ensure the structural integrity under high temperature sudden change environments. Thirdly, silicon whiskers themselves have good high temperature resistance, which can improve the spray coating layer to maintain structural stability, reduce deformation and damage even in a long-term high temperature environment, and ensure that the spray coating layer maintains a good use state. Finally, the uniform dispersion of silicon whiskers in the spray coating matrix can increase the interface contact area between the whiskers and the matrix material, strengthen the bonding force between the whiskers and the matrix through physical adsorption and chemical bonding, and thus improve the overall performance of the spray coating layer. The introduction of silicon whiskers in the present invention utilizes the classical theory of composite material reinforcement, that is, the crack propagation is hindered by highly oriented or randomly distributed high-strength, high-modulus whiskers, and the good interaction between the whiskers and the matrix enhances the integrity of the spray coating layer. In addition, the small size effect and quantum size effect of silicon whiskers also have a positive impact on the performance of the spray coating, such as reducing the thermal expansion coefficient, etc., which together promote the long-term stable operation of the spray coating under harsh working conditions.
[0017] The present invention adopts a composite hydrophobic agent, which is composed of polydimethylsiloxane and fluorine-modified polyurethane, and the mass percentage of the raw material components is: polydimethylsiloxane is 75%, and fluorine-modified polyurethane is 25%. The composite hydrophobic agent has the following functions: first, by forming a hydrophobic layer on the surface of the material particles, the amount of water added to the spray coating is reduced. Polydimethylsiloxane is a highly efficient hydrophobic material because the organic silicon group in its molecule can effectively repel moisture, and fluorine-modified polyurethane further enhances the hydrophobic effect by introducing fluorine elements, because fluorine atoms have extremely low surface energy, making it difficult for water to spread on its surface. The composite hydrophobic layer formed by the combination of the two significantly reduces the water addition rate of the spray coating; secondly, the hydrophobic layer can effectively isolate the direct contact between oxygen in the air and the refractory material, reduce oxidation corrosion, and slow down the oxidation rate of the spray coating layer at high temperature, thereby extending its service life; finally, by forming a hydrophobic barrier on the surface of the spray coating material, the chemical reaction opportunities between harmful components in the molten steel (such as oxides, sulfides, etc.) and the refractory material are reduced, the corrosion resistance is improved, the refractory substrate is protected from corrosion, and its good thermal insulation and corrosion resistance are maintained. The composite hydrophobic agent is evenly distributed on the surface of the spray coating material or in the micropores by chemical bonding or physical adsorption to form a dense protective layer. The low surface energy characteristics of polydimethylsiloxane and the special fluorine chain structure of fluorine-modified polyurethane work together to reduce the water addition rate of the spray coating and indirectly enhance the strength, thermal stability and durability of the spray coating layer.
[0018] The present invention adopts sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate to form a composite binder system, and its functions are as follows: firstly, sodium metasilicate nonahydrate is a water-soluble silicate with strong alkalinity, which is used to improve the bonding strength and adjust the fluidity of the spray coating. It is hydrolyzed in water to generate silicic acid, which then reacts with active oxides (such as MgO) in refractory materials to generate hydrated silicate, thereby enhancing the internal bonding force of the spray coating layer and improving the overall strength and durability of the spray coating layer. An appropriate amount of sodium metasilicate nonahydrate can also adjust the slurry viscosity of the spray coating, so that it has good construction performance and is convenient for spraying operation. At the same time, it can promote the curing and hardening process of the spray coating during drying or heating. Secondly, polyvinyl alcohol is a water-soluble polymer, which is used to enhance the bonding property of the spray coating and improve the water retention property. It has good film-forming property and bonding force. In the spray coating, it can form a continuous polymer network structure, enhance the bonding between particles through physical entanglement and hydrogen bonding, and improve the crack resistance and toughness of the spray coating layer. Polyvinyl alcohol can absorb and retain more water, which helps the spray paint to remain moist before hardening, slows down the drying speed, makes the bonding reaction more complete, and improves the density and strength of the spray paint layer; finally, sodium tripolyphosphate, as a highly efficient dispersant, can improve the leveling and dispersibility of the spray paint, increase the bonding strength at high temperatures, and effectively reduce the electrostatic attraction and van der Waals force between the spray paint particles, prevent particle agglomeration, and make the solid particles in the spray paint system more evenly dispersed, thereby improving the strength, stability and uniformity of the spray paint, and helping to form a smooth and flat spray paint layer surface, improving the surface quality and aesthetics, and enhancing corrosion resistance. These three composite binders cooperate with each other through their respective chemical properties and physical effects, jointly promoting the transformation of the spray coating from the rheological state to the solid state, and forming a strong bonding network during the transformation process, thereby enhancing the structural strength, construction performance and final use performance of the spray coating layer. Sodium metasilicate nonahydrate provides initial bonding force through chemical reaction, polyvinyl alcohol strengthens the structure through the entanglement of polymer chains, and sodium tripolyphosphate ensures the uniformity and construction convenience of the spray coating through dispersion. The synergistic effect of the three significantly improves the overall performance of the magnesium spray coating.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention significantly improves the refractoriness, density, structural stability and thermal conductivity of the spray coating by introducing 800 mesh 95 magnesia sand and 600 mesh quicklime ultrafine powder, effectively resists high-temperature molten steel erosion and thermal shock damage, and optimizes the construction performance;
[0021] 2. The present invention adds silicon whiskers as a reinforcing phase, which significantly enhances the mechanical properties, thermal physical properties and thermal shock resistance of the spray coating and prolongs its service life;
[0022] 3. The present invention adopts a composite hydrophobic agent composed of polydimethylsiloxane and fluorine-modified polyurethane, which reduces the water addition rate, reduces oxidation corrosion, and improves corrosion resistance;
[0023] 4. The present invention uses a composite binder system composed of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate, which strengthens the bonding force, fluidity, dispersibility and construction performance of the spray coating layer, ensuring the high strength, durability and aesthetics of the spray coating layer.
[0024] In summary, compared with the traditional process, the construction water addition rate of the tundish spray coating of the present invention is significantly reduced, the comprehensive strength of the spray coating is greatly enhanced, the risk of cracking after drying is reduced, the service life of the spray coating is extended, the construction efficiency, construction performance and continuity of continuous casting operations are improved, the production cost is reduced, and the product quality is improved. In addition, reducing the use of water is conducive to energy conservation and emission reduction, which is in line with the concept of green manufacturing. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The present invention provides a technical solution for tundish spray coating:
[0027] A tundish spray coating, wherein the mass percentages of various raw material components in the tundish spray coating are: 22-25% of 3-1mm 91 magnesia sand, 46-51% of 1-0mm 94 magnesia sand, 16-20% of 200-mesh 94 magnesia sand, 1.5-3% of 800-mesh 95 magnesia sand, 2-3% of silica fume, 2-3% of quicklime, 0.1-0.15% of silicon whisker, 0.4-0.6% of 70 cement, 0.6-0.8% of sodium metasilicate nonahydrate, 0.3-0.5% of polyvinyl alcohol, 0.01-0.03% of composite hydrophobic agent, 0.5-0.7% of paper fiber, 0.01% of organic fiber, 0.02-0.03% of metal aluminum powder, 0.2-0.3% of sodium tripolyphosphate, and 0.1-0.3% of citric acid.
[0028] As a preferred embodiment of the present invention, the tundish spray coating comprises 23% 3-1 mm 91 magnesia sand, 49% 1-0 mm 94 magnesia sand, 18% 200 mesh 94 magnesia sand, 2% 800 mesh 95 magnesia sand, 2.4% silica fume, 2.7% quicklime, 0.12% silicon whisker, 0.5% 70 cement, 0.7% sodium metasilicate nonahydrate, 0.43% polyvinyl alcohol, 0.02% composite hydrophobic agent, 0.6% paper fiber, 0.01% organic fiber, 0.02% metal aluminum powder, 0.3% sodium tripolyphosphate, and 0.2% citric acid.
[0029] The present invention adopts 3-1mm 91 magnesia sand, which can play a skeleton role in the coating, help to form a solid structure, and improve the overall strength and wear resistance of the coating; adopts 1-0mm 94 magnesia sand, and the medium-sized magnesia sand fills the gaps between larger particles, making the coating denser, reducing the porosity, and improving the permeability resistance and erosion resistance; adopts 200-mesh fine powder 94 magnesia sand, which helps to form a smoother coating surface and fill smaller gaps, further enhancing the density and uniformity of the coating. At the same time, high-purity 91 magnesia sand and 94 magnesia sand both have high refractoriness and erosion resistance, and can maintain the stability and durability of the coating under high temperature and corrosive environments; the present invention adopts an appropriate amount of 70 cement as a binder, which can firmly bond magnesia sand particles of different particle sizes together to form a solid coating. The addition of an appropriate amount of cement not only ensures the strength of the coating, but also avoids the embrittlement of the coating caused by excessive cement; the addition of paper fiber and organic fiber improves the toughness and spalling resistance of the coating, helps prevent the coating from cracking and falling off under high temperature and mechanical stress, and is particularly effective in improving thermal shock resistance.
[0030] As a preferred embodiment of the present invention, the sum of the mass percentages of 800-mesh 95 magnesia sand, silica ash and quicklime in the tundish spray coating is 6.2-8.4%, the SiO2 content in the silica ash is ≥94%; the quicklime particle size is 600 mesh and the purity is 98%.
[0031] The present invention adopts 800-mesh 95 magnesia sand and 600-mesh quicklime ultrafine powder, aiming to improve the performance of the spray coating and optimize the molten steel purification ability. The 800-mesh 95 magnesia sand has high purity and low impurities through high-temperature smelting, which significantly improves the refractoriness and corrosion resistance of the spray coating, especially under the impact of high-temperature molten steel, it can effectively prevent thermal shock damage. In addition, its fine powder particle size helps to form a dense working layer, reduce porosity, enhance overall stability and permeability, thereby preventing the erosion of non-metallic inclusions; 600-mesh quicklime releases heat when it meets water in the spray coating and is converted into slaked lime, which promotes sintering and hardening, and improves overall strength and spalling resistance. As an alkaline substance, quicklime can adjust the alkalinity of the spray coating, effectively inhibit acid corrosion, and protect the spray coating layer. In addition, the appropriate addition of quicklime can improve the construction performance, improve the fluidity and wall hanging performance, ensure the continuity and integrity of the spray coating, and at the same time, high-purity quicklime can reduce the additional costs and environmental pollution problems caused by impurity discharge treatment, and at the same time improve the utilization rate of the coating and the service life of the tundish, thereby reducing the overall production cost; silica ash has a very small particle size and a high specific surface area, which can fill the tiny pores in the coating, improve the density and strength of the coating, and at the same time, silica ash can also react chemically with other components in the coating to generate a harder substance, further enhancing the wear resistance of the coating. SiO2 is one of the main components of silica ash, and its high content helps to enhance the overall strength and hardness of the coating. This enables the tundish spray coating to maintain better stability when subjected to high temperature, high pressure and corrosive media, and reduces the risk of coating damage and peeling; the present invention can adjust the thermal conductivity and thermal expansion coefficient of the coating to a certain extent by adjusting the ratio of 95 magnesium sand, silica ash and quicklime, so that it can better adapt to the working environment of the tundish at high temperature. This helps to reduce problems such as cracking or shedding of the coating caused by temperature changes.
[0032] As a preferred embodiment of the present invention, the SiO2 content of the silicon whisker is ≥99.9%, the fiber length is 2 to 10 μm, and the bulk density is 0.78 g·cm 3 , the true density is 2.2~2.4g·cm 3 , refractoriness is 1720℃, Mohs hardness is 7, and loss on ignition is ≤0.10%.
[0033] The invention adopts silicon whiskers with high refractoriness. In an extremely high temperature environment, the silicon whiskers can maintain stable chemical and physical properties and are not easy to melt or decompose. Therefore, adding silicon whiskers to the tundish spray coating can significantly improve the refractory performance of the coating, so that the coating can withstand the erosion of high-temperature liquids such as molten steel without failure. The low ignition loss indicates that the silicon whiskers have good stability at high temperatures and are not easy to volatilize or decompose to generate gas, which helps to reduce the mass loss and pore formation of the coating at high temperatures, thereby maintaining the integrity and density of the coating. The silicon whiskers with a Mohs hardness of 7 can enhance the hardness and wear resistance of the coating. Under the scouring and erosion of high-temperature liquids such as molten steel, the high-hardness spray coating can better resist wear and scratches, thereby extending the service life of the tundish. The fiber body length of 2 to 10 μm enables the silicon whiskers to form an effective fiber network structure in the spray coating, which helps to enhance the strength and toughness of the coating and improve the crack resistance and spalling resistance of the coating. The bulk density is 0.78 g cm 3 , the true density is 2.2~2.4g·cm 3 , indicating that silicon whiskers have a larger specific surface area and porosity, and can form more micropores and interfaces in the spray coating, which helps to enhance the adsorption and reactivity of the spray coating. At the same time, the microporous structure also helps to improve the air permeability and thermal stability of the spray coating.
[0034] As a preferred embodiment of the present invention, the composite hydrophobic agent has the following raw material components in percentage by weight: polydimethylsiloxane is 75% and fluorine-modified polyurethane is 25%.
[0035] The present invention adopts a composite hydrophobic agent composed of 75% polydimethylsiloxane and 25% fluorine-modified polyurethane, which is evenly distributed on the surface of the spray coating material or in the micropores by chemical bonding or physical adsorption to form a dense protective layer. The low surface energy characteristics of polydimethylsiloxane and the special fluorine chain structure of fluorine-modified polyurethane work together to reduce the water addition rate of the spray coating and indirectly enhance the strength, thermal stability and durability of the spray coating layer.
[0036] As a preferred embodiment of the present invention, the sodium metasilicate nonahydrate, polyvinyl alcohol, sodium tripolyphosphate and citric acid in the tundish spray coating are all of industrial grade.
[0037] The invention selects sodium metasilicate nonahydrate, polyvinyl alcohol, sodium tripolyphosphate and citric acid as industrial-grade additives, which have many advantages in preparing the tundish spray coating. The sodium metasilicate nonahydrate provides initial bonding force through chemical reaction, polyvinyl alcohol strengthens the structure through the winding of polymer chains, sodium tripolyphosphate ensures the uniformity and construction convenience of the spray coating through dispersion, and citric acid ensures the stability of the spray coating by adjusting the pH value in the spray coating. The synergistic effect of the four can significantly improve the fluidity and pumpability, adhesion, durability, dispersibility, stability and corrosion resistance of the spray coating, thereby improving the overall performance and quality of the tundish spray coating.
[0038] As a preferred embodiment of the present invention, the sum of the mass percentages of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate in the tundish spray coating is ≥1.15%.
[0039] The present invention adjusts the mixing ratio of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate. The synergistic effect of these additives can significantly improve the performance of the tundish spray coating to a certain extent. They work together on the bonding strength, fluidity, adhesion, durability and other aspects of the spray coating, making the spray coating more suitable for the use environment of the tundish, and improving production efficiency and product quality.
[0040] As a preferred embodiment of the present invention, the metal aluminum powder has a particle size of 80 mesh and an Al content of ≥98%.
[0041] The high melting point of aluminum powder enables it to remain stable in high temperature environments and is not easy to melt or evaporate, thereby enhancing the fire resistance of the tundish spray coating. The 80-mesh aluminum powder has a moderate particle size and can be evenly distributed in the coating during the spraying process to avoid agglomeration and precipitation, ensuring the uniformity and consistency of the coating, increasing the cohesion of the spray coating, making it more durable, and improving the overall mechanical strength of the tundish.
[0042] Specific implementation cases:
[0043] A specific embodiment of the tundish spray coating material of the present invention is provided below.
[0044] Embodiment 1:
[0045] The present embodiment provides a tundish spray coating, wherein the tundish spray coating comprises, by mass percentage, 23% of 91 magnesia sand of 3-1 mm, 49% of 94 magnesia sand of 1-0 mm, 18% of 94 magnesia sand of 200 mesh, 2% of 95 magnesia sand of 800 mesh, 2.4% of silica fume, 2.7% of quicklime, 0.12% of silicon whisker, 0.5% of 70 cement, 0.7% of sodium metasilicate nonahydrate, 0.43% of polyvinyl alcohol, 0.02% of composite hydrophobic agent, 0.6% of paper fiber, 0.01% of organic fiber, 0.02% of metal aluminum powder, 0.3% of sodium tripolyphosphate, and 0.2% of citric acid.
[0046] Embodiment 2:
[0047] The present embodiment provides a tundish spray coating, wherein the tundish spray coating comprises, by mass percentage, 22% of 91 magnesia sand of 3-1 mm, 51% of 94 magnesia sand of 1-0 mm, 16% of 94 magnesia sand of 200 mesh, 3% of 95 magnesia sand of 800 mesh, 2.3% of silica fume, 3% of quicklime, 0.14% of silicon whisker, 0.54% of 70 cement, 0.6% of sodium metasilicate nonahydrate, 0.4% of polyvinyl alcohol, 0.01% of composite hydrophobic agent, 0.63% of paper fiber, 0.01% of organic fiber, 0.03% of metal aluminum powder, 0.24% of sodium tripolyphosphate, and 0.1% of citric acid.
[0048] Embodiment 3:
[0049] The present embodiment provides a tundish spray coating, wherein the tundish spray coating comprises, by mass percentage, 24% of 91 magnesia sand of 3-1 mm, 47.5% of 94 magnesia sand of 1-0 mm, 19% of 94 magnesia sand of 200 mesh, 1.7% of 95 magnesia sand of 800 mesh, 2.6% of silica fume, 2% of quicklime, 0.13% of silicon whisker, 0.6% of 70 cement, 0.68% of sodium metasilicate nonahydrate, 0.5% of polyvinyl alcohol, 0.02% of composite hydrophobic agent, 0.7% of paper fiber, 0.01% of organic fiber, 0.02% of metal aluminum powder, 0.3% of sodium tripolyphosphate, and 0.24% of citric acid.
[0050] Embodiment 4:
[0051] The present embodiment provides a tundish spray coating, wherein the tundish spray coating comprises, by mass percentage, 23% of 91 magnesia sand of 3-1 mm, 48% of 94 magnesia sand of 1-0 mm, 18.5% of 94 magnesia sand of 200 mesh, 2.2% of 95 magnesia sand of 800 mesh, 3% of silica fume, 2.7% of quicklime, 0.1% of silicon whisker, 0.44% of 70 cement, 0.64% of sodium metasilicate nonahydrate, 0.3% of polyvinyl alcohol, 0.02% of composite hydrophobic agent, 0.54% of paper fiber, 0.01% of organic fiber, 0.03% of metal aluminum powder, 0.22% of sodium tripolyphosphate, and 0.3% of citric acid.
[0052] Embodiment 5:
[0053] The present embodiment provides a tundish spray coating, wherein the tundish spray coating comprises, by mass percentage, 23% of 91 magnesia sand of 3-1 mm, 50% of 94 magnesia sand of 1-0 mm, 18% of 94 magnesia sand of 200 mesh, 1.5% of 95 magnesia sand of 800 mesh, 2.5% of silica fume, 2.2% of quicklime, 0.15% of silicon whisker, 0.51% of 70 cement, 0.8% of sodium metasilicate nonahydrate, 0.41% of polyvinyl alcohol, 0.03% of composite hydrophobic agent, 0.5% of paper fiber, 0.01% of organic fiber, 0.03% of metal aluminum powder, 0.2% of sodium tripolyphosphate, and 0.16% of citric acid.
[0054] Embodiment 6:
[0055] The present embodiment provides a tundish spray coating, wherein the tundish spray coating comprises, by mass percentage, 25% of 91 magnesia sand of 3-1 mm, 46% of 94 magnesia sand of 1-0 mm, 20% of 94 magnesia sand of 200 mesh, 1.8% of 95 magnesia sand of 800 mesh, 2% of silica fume, 2.5% of quicklime, 0.11% of silicon whisker, 0.4% of 70 cement, 0.73% of sodium metasilicate nonahydrate, 0.36% of polyvinyl alcohol, 0.01% of composite hydrophobic agent, 0.58% of paper fiber, 0.01% of organic fiber, 0.02% of metal aluminum powder, 0.27% of sodium tripolyphosphate, and 0.21% of citric acid.
[0056] Comparative Example 1:
[0057] The present comparative example provides a tundish spray coating, wherein the tundish spray coating has the following components in percentage by mass: 3-1 mm 91 magnesia is 22%, 1-0 mm 94 magnesia is 51%, 200 mesh 94 magnesia is 16%, 800 mesh 95 magnesia is 3%, silica fume is 2.3%, quicklime is 3%, silicon whisker is 0.14%, 70 cement is 0.54%, sodium metasilicate nonahydrate is 0.6%, polyvinyl alcohol is 0.4%, paper fiber is 0.64%, organic fiber is 0.01%, metal aluminum powder is 0.03%, sodium tripolyphosphate is 0.24%, citric acid is 0.1%, and the present comparative example does not contain a composite hydrophobic agent.
[0058] Comparative Example 2:
[0059] The present comparative example provides a tundish spray coating, wherein the tundish spray coating comprises, by mass percentage, 24.5% of 91 magnesia sand of 3-1 mm, 47.5% of 94 magnesia sand of 1-0 mm, 19% of 94 magnesia sand of 200 mesh, 1.7% of 95 magnesia sand of 800 mesh, 2.6% of silica fume, 2% of quicklime, 0.13% of silicon whisker, 0.6% of 70 cement, 0.68% of sodium metasilicate nonahydrate, 0.02% of composite hydrophobic agent, 0.7% of paper fiber, 0.01% of organic fiber, 0.02% of metal aluminum powder, 0.3% of sodium tripolyphosphate, and 0.24% of citric acid in the tundish spray coating. The present comparative example does not contain polyvinyl alcohol.
[0060] Comparative Example 3:
[0061] The present comparative example provides a tundish spray coating, wherein the tundish spray coating has the following components in percentage by mass: 3-1 mm 91 magnesia sand is 23.64%, 1-0 mm 94 magnesia sand is 48%, 200 mesh 94 magnesia sand is 18.5%, 800 mesh 95 magnesia sand is 2.2%, silica fume is 3%, quicklime is 2.7%, silicon whisker is 0.1%, 70 cement is 0.44%, polyvinyl alcohol is 0.3%, composite hydrophobic agent is 0.02%, paper fiber is 0.54%, organic fiber is 0.01%, metal aluminum powder is 0.03%, sodium tripolyphosphate is 0.22%, citric acid is 0.3%, and sodium metasilicate nonahydrate is not contained in the present comparative example.
[0062] Comparative Example 4:
[0063] The present comparative example provides a tundish spray coating, wherein the tundish spray coating comprises, by mass percentage, 23.15% of 91 magnesia sand of 3-1 mm, 50% of 94 magnesia sand of 1-0 mm, 18% of 94 magnesia sand of 200 mesh, 1.5% of 95 magnesia sand of 800 mesh, 2.5% of silica fume, 2.2% of quicklime, 0.51% of 70 cement, 0.8% of sodium metasilicate nonahydrate, 0.41% of polyvinyl alcohol, 0.03% of composite hydrophobic agent, 0.5% of paper fiber, 0.01% of organic fiber, 0.03% of metal aluminum powder, 0.2% of sodium tripolyphosphate, and 0.16% of citric acid in the tundish spray coating, and the present comparative example does not contain silicon whiskers.
[0064] The present invention prepares samples of a tundish spray coating of Examples 1 to 6 and Comparative Examples 1 to 4 according to GB / T4513.5-2017 "Monomorphous Refractory Materials Part 5: Sample Preparation and Pretreatment" for sample preparation, and the tests of bulk density, linear change rate, flexural strength and compressive strength are carried out according to the test method in GB / T 4513.6-2017 "Monomorphous Refractory Materials Part 6: Determination of Physical Properties". The qualified product detection index range is: water addition rate is ≤15%; fluidity is ≥167mm; the sum of the mass percentages of 95 magnesia sand, silica fume and quicklime of 800 mesh is 6.2-8.4%; the sum of the mass percentages of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate is ≥1.15%; the linear change rate (1100°C / 3h) is -0.8 ~0%, linear change rate (1550℃ / 3h) is -2.2~0%; flexural strength (110℃) is ≥2.5MPa, flexural strength (1100℃ / 3h) is ≥1.5MPa, flexural strength (1550℃ / 3h) is ≥3.5MPa; compressive strength (110℃) is ≥9MPa, compressive strength (1100℃ / 3h) is ≥3MPa, compressive strength (1550℃ / 3h) is ≥10MPa; construction performance is good. Test results are shown in Table 1:
[0065] Table 1 Test results of Examples 1 to 6 and Comparative Examples 1 to 4
[0066]
[0067] Comparative Example 1 is based on Example 2, but the introduction of the composite hydrophobic agent is cancelled and the paper fiber is increased accordingly. As can be seen from Table 1, compared with Example 2, the water addition rate and the linear change rate of Comparative Example 1 are significantly increased, the fluidity, flexural strength and compressive strength are significantly decreased, the construction performance is poor, and the test results are unqualified. The test effect of Comparative Example 1 is significantly lower than that of Example 2.
[0068] Comparative Example 2 is based on Example 3, but the introduction of polyvinyl alcohol is cancelled, and 3-1 mm 91 magnesium sand is correspondingly increased. It can be seen from Table 1 that compared with Example 3, the sum of the mass percentages of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate in Comparative Example 2 is too low, the flexural strength and compressive strength are significantly reduced, the workability is poor, the test results are unqualified, and the test effect of Comparative Example 2 is significantly lower than that of Example 3.
[0069] Comparative Example 3 is based on Example 4, but the introduction of sodium metasilicate nonahydrate is cancelled, and 3-1 mm 91 magnesium sand is correspondingly increased. As can be seen from Table 1, compared with Example 4, the sum of the mass percentages of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate in Comparative Example 3 is too low, the flexural strength and compressive strength are significantly reduced, the workability is poor, the test results are unqualified, and the test effect of Comparative Example 3 is significantly lower than that of Example 4.
[0070] Comparative Example 4 is based on Example 5, but the introduction of silicon whiskers is cancelled, and 3-1 mm 91 magnesia sand is correspondingly added. As can be seen from Table 1, compared with Example 5, the flexural strength and compressive strength of Comparative Example 4 at 110°C are significantly reduced, the workability is general, and the test results are unqualified. The test effect of Comparative Example 4 is significantly lower than that of Example 5.
[0071] In summary, the present invention can effectively improve the flexural strength and compressive strength of the tundish spray coating by adding a composite hydrophobic agent, polyvinyl alcohol, sodium metasilicate nonahydrate and silicon whiskers, reduce the risk of cracking after drying, and significantly improve the construction performance. By adding a composite hydrophobic agent, the water addition rate is significantly reduced. By setting a reasonable ratio of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate, their synergistic effect in the spray coating can significantly improve the bonding strength, fluidity, adhesion, durability and corrosion resistance of the spray coating, thereby improving the service life and performance stability of the spray coating, reducing production costs and improving product quality.
[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A tundish spray coating, characterized in that: The mass percentage of each raw material component in the tundish spray coating is as follows: 3-1mm 91 magnesia sand is 22-25%, 1-0mm 94 magnesia sand is 46-51%, 200 mesh 94 magnesia sand is 16-20%, 800 mesh 95 magnesia sand is 1.5-3%, silica fume is 2-3%, quicklime is 2-3%, silicon whisker is 0.1-0.15%, 70 cement is 0.4-0.6%, sodium metasilicate nonahydrate is 0.6-0.8%, polyvinyl alcohol is 0.3-0.5%, composite hydrophobic agent is 0.01-0.03%, paper fiber is 0.5-0.7%, organic fiber is 0.01%, metal aluminum powder is 0.02-0.03%, sodium tripolyphosphate is 0.2-0.3%, and citric acid is 0.1-0.3%.
2. The tundish spray coating material according to claim 1, characterized in that: The tundish spray coating material comprises 23% of 3-1 mm 91 magnesia sand, 49% of 1-0 mm 94 magnesia sand, 18% of 200 mesh 94 magnesia sand, 2% of 800 mesh 95 magnesia sand, 2.4% of silica fume, 2.7% of quicklime, 0.12% of silicon whisker, 0.5% of 70 cement, 0.7% of sodium metasilicate nonahydrate, 0.43% of polyvinyl alcohol, 0.02% of composite hydrophobic agent, 0.6% of paper fiber, 0.01% of organic fiber, 0.02% of metal aluminum powder, 0.3% of sodium tripolyphosphate and 0.2% of citric acid.
3. The tundish spray coating material according to claim 1, characterized in that: The sum of the mass percentages of 800-mesh 95 magnesia sand, silica fume and quicklime in the tundish spray coating is 6.2-8.4%.
4. The tundish spray coating material according to claim 3, characterized in that: The SiO2 content in the silica ash is ≥94%; the quicklime particle size is 600 meshes and the purity is 98%.
5. The tundish spray coating material according to claim 1, characterized in that: The silicon whisker has a SiO2 content of ≥99.9%, a fiber length of 2 to 10 μm, and a bulk density of 0.78 g·cm 3 , the true density is 2.2~2.4g·cm 3 , refractoriness is 1720℃, Mohs hardness is 7, and loss on ignition is ≤0.10%.
6. The tundish spray coating material according to claim 1, characterized in that: The composite hydrophobic agent has the following raw material components in percentage by weight: 75% polydimethylsiloxane and 25% fluorine-modified polyurethane.
7. The tundish spray coating material according to claim 1, characterized in that: The sodium metasilicate nonahydrate, polyvinyl alcohol, sodium tripolyphosphate and citric acid in the tundish spray coating are all of industrial grade.
8. The tundish spray coating material according to claim 7, characterized in that: The sum of the mass percentages of sodium metasilicate nonahydrate, polyvinyl alcohol and sodium tripolyphosphate in the tundish spray coating is ≥1.15%.
9. The tundish spray coating material according to claim 1, characterized in that: The metal aluminum powder has a particle size of 80 meshes and an Al content of ≥98%.
Citation Information
Patent Citations
Tundish coating
CN103833394A
Spray-repairing material used for sintering large flue and having excellent bonding performance and preparation method
CN107032810A
Method for preparation of high performance magnesia carbon brick by adding silicon carbide whisker
CN108440009A
Refractory material for metallurgical package and preparation method of refractory material
CN110423127A
Sidewalk and construction process thereof
CN111170696A
